Recurrent intussusception with ileal perforation as a complication of Blue Rubber Bleb Nevus Syndrome in a pediatric patient - Portia Heidi M. Balite; Ma. Celine Isobel A. Villegas (Elsevier, 2023)
Blue rubber bleb nevus syndrome (BRBNS) is a rare congenital condition, characterized by multiple venous malformations that may involve any organ system, most commonly the skin or the gastrointestinal tract. These lesions are often responsible for chronic blood loss and secondary anemia, and in rare situations may cause severe complications such as intussusception, volvulus, and intestinal infarction. Intussusception as a complication of BRBNS, although a known complication of the disease, has rarely been reported, especially in the Philippines. In the Philippine Society for Orphan Disorders, only 2 cases of BRBNS are currently included in the organization, including the patient presented in the case report. The treatment of BRBNS that involves the gastrointestinal tract depends on the extent of intestinal involvement and severity of the disease. The treatment aims to preserve the GI tract as much as possible due to the high recurrence in the disease. In this case report, we present a 13 year-old male with BRBNS with previous history of intussusception, successfully managed conservatively; however, upon recurrence, underwent exploratory laparotomy wherein a subcentimeter perforation in the antimesenteric border of the proximal ileum was noted, together with a gangrenous intussuscipiens, and multiple mulberry-like formations on the antimesenteric border of the small bowels. Histopathological findings of the resected bowels showed multiple cavernous hemangiomas consistent with BRBNS. The postoperative course of the patient was unremarkable.